Prototipe Pengendali Pintu Darurat Menggunakan Mikrokontroler ATMega 16 - Zain, Abdul; Muliawan, Arief (INTEK: Jurnal Penelitian, 2018)
In a building should have a good security system,especially Emergency Exit (emergency evacuation path).Emergency Exit is important because when an emergency occursin the building, the first thing to do is get out of the lab building.One thing to note is the emergency exit door. With the emergencydoor that can be opened quickly so all workers can get outquickly as well from the building when an emergency occurs.So,we need a model (prototype) controlling an emergency door thatcan function properly in an emergency. Prototype newemergency door controller is expected to be implemented intoactual emergency door. Prototype can be accessed with a pushbutton by the user facility. The prototype controller usemicrocontroller ATMega16. And for each emergency exitmovement is monitored and its status is expressed in LEDindicator lights and LCD display on 16x2. Modeling controllingemergency exit of a series of tests using a prototype have workedwell except on the 3rd test caused an error when calibrating thedistance between Ultrasonic sensor with Emergency Door.